Construction of carbon dots modified hollow g-C3N4 spheres via in situ calcination of cyanamide and glucose for highly enhanced visible light photocatalytic hydrogen evolution. (8th January 2022) - Ding, Yuan; Lin, Zhi; Deng, Jiawei; Liu, Yingliang; Zhang, Li; Wang, Kunlun; Xu, Shengang; Cao, Shaokui
Abstract: In this work, a series of carbon dots (CDs) modified hollow g-C3 N4 spheres (HCNS-Cx ) were constructed via a double in situ approach using cyanamide and glucose as precursors, respectively. As HCNS-Cx was synthesized by one-step in situ thermal polymerization of two precursors, which could make CDs and g-C3 N4 keep tight connection and increase the separation of the photogenerated electron-hole pairs. The average diameter and wall thickness of the HCNS-Cx are about 355 nm and 55 nm, respectively. Under the visible light irradiation, the H2 evolution rate (HER) of HCNS-C1.0 (2322 μmol g −1  h −1 ) was 19 times that of bulk g-C3 N4 (122 μmol g −1  h −1 ) and 1.8 times that of HCNS without CDs modification (1289 μmol g −1  h −1 ), respectively. And its apparent quantum efficiency is 17.93% at 420 nm. The specific surface area, light absorption capacity, and charge carrier mobility of HCNS-Cx could be dramatically improved due to the introduction of CDs and hollow structures of g-C3 N4 spheres, resulting in a significant improvement of photocatalytic activity. Graphical abstract: Image 1 Highlights: Carbon dots modified hollow g-C3 N4 spheres were constructed via an in situ approach. The hollow sphere structure could increase the specific surface area and light absorption capacity. CDs could decrease the recombination of electron-hole pairs significantly. HER of HCNS–C1.0 is 19 times higher than that of BCN.